Clinical Evaluation of Retention, Stability, Esthetics, Occlusion, and Tissue Response of Acrylic, Flexible, and Cobalt-Chromium Removable Partial Dentures - Hayder Mohammed (International Journal of Medical Science and Pharmaceutical Research, 2026)
Background: For patients who are partially edentulous, removable partial dentures RPDs are a crucial therapy option. Prosthesis material, retention, stability, occlusion, esthetics, and interaction with supporting oral tissues all have an impact on their clinical performance. Objective: To compare and clinically assess the retention, stability, esthetics, occlusion, and tissue response of acrylic resin, flexible thermoplastic, and cobalt-chromium RPDs. Materials and Methods: Thirty-seven acrylic resin, thirteen flexible thermoplastics and ten cobalt-chromium RPDs were among the sixty patients who received clinical examinations. Retention and stability were graded as good, fair, or poor; esthetics and occlusion as acceptable or unacceptable; and tissue response as favorable or unfavorable. Frequencies and percentages were calculated. Comparisons among groups were performed using exact Monte Carlo testing based on the Pearson Chi-square statistic, with significance set at P < 0.05. Results: 43.2% of acrylic, 76.9% of flexible, and 90.0% of cobalt-chromium RPDs showed good retention; with a significant difference (P = 0.043). Good stability was recorded in 40.5%, 76.9%, and 90.0%, respectively with a significant difference (P = 0.027). Acceptable esthetics occurred in 83.8%, 92.3%, and 90.0% with a non-significant difference (P = 0.778). Acceptable occlusion occurred in 64.9%, 76.9%, and 90.0% with a non-significant difference (P = 0.284). Favorable tissue response was observed in 51.4%, 76.9%, and 90.0%, respectively with a significant difference (P = 0.043). Conclusion: Cobalt-chromium RPDs demonstrated the best favorable overall clinical performance particularly for retention, stability, and tissue response. Flexible RPDs also showed favorable results, whereas acrylic RPDs exhibited fewer favorable findings. Esthetic and occlusal differences were not statistically significant.